Product Innovation for Sustainable Competitive Advantage through Strarbucks Coffee Marketing Perfome in Malang - Tri Sugiarti Ramadhan; Eka Farida (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: This study aims to identify the factors influencing product innovation that will form a sustainable competitive advantage that will affect marketing performance. Design/methodology/approach: This study uses four hypotheses that are tested using Structural Equation Modeling (SEM) using AMOS 18 software. For 101 respondents. Findings: The results of this study indicate that: a) Product Innovation (X) has a significant effect on competitive advantage (Z). b) Product Innovation (X) has a significant effect on Marketing Performance (Y). c) Sustainable Competitive Advantage (Z) has a significant effect on Marketing Performance (Y) d) Product Innovation (X) has a significant effect on Marketing Performance (Y) through Sustainable Competitive Advantage (Y) and SEM data processing for the full model has met the following fit criteria, chi-square = 36.7; probability = 0.000; GFI = 0.72; AGFI = 0.653; CFI = 0.36; TLI = 0.276; RMSEA = 0.109; CMIN/DF = 2.18. As a result, greater product innovation will affect marketing performance and further build a sustainable competitive advantage. Practical implications: Based on the research, it can be concluded that Android-based accounting learning media has fulfilled the requirements for validity, practicality and has a good potential effect on student learning activities and outcomes. So that Android-based accounting learning media can be used as an alternative teacher in teaching accounting material for adjusting journal entries. Paper type: Research paper